Tuvan work of literature in anthologies of modern literature of the peoples of Russia: dimensions of poetry, prose, drama - Arzamazov, Alexey A.; Dolzhikova, Angela V. (The New Research of Tuva, 2024)
The article examines the work of Tuvan authors included in the anthology of modern literature for the peoples of Russia: Modern literature of the peoples of Russia. Poem. Anthology (2017), Modern literature of the peoples of Russia. Prose. Anthology (2018), Modern literature of the peoples of Russia. Drama. Anthology (2020). Poetic, prose, and dramatic texts have been selected for the study, which together allow us to draw conclusions about the general state and trends in the development of Tuvan literature at the turn of the XX–XXI centuries. It has been established that Tuvan literature, in comparison to many other literary traditions among the peoples of Russia, is characterized by both a high level of artistic quality and a diverse range of styles and creative approaches. The study identified several significant features that are specific to Tuvan literature: the realization of the expressive potential of natural symbolism, the regular construction of a person’s spatial reality, an increased focus on historical events and characters, a deep psychological dimension, and the widespread use of visual techniques. It has been concluded that Tuvan literature possesses a high degree of artistic expression of its ethnocultural component. It is evident that Tuvan literature maintains its linguistic independence and linguistic and cultural distinctiveness. Based on the data from the anthologies, we attempt to identify key strategies for the evolution of the literary traditions of peoples in Russia.